Chemical Constituents of Salvia przewalskii Maxim. - Yang, Yang; Bing, Zhu; Sun, Lianna; Wu, Zhijun; Chen, Wansheng (Asian Journal of Chemistry, 2012)
In order to investigate the biologically active constituents of the Salvia przewalskii Maxim., a new diterpenoid, named isoganxinonic acid A (1), together with g-linolenic acid (2), tanshinol B (3), cryptotanshinone (4), paeoniflorin (5), protocatechualdehyde (6), protocatechuic acid (7), caffeic acid (8), rosmarinic acid (9) and salvianolic acid B (10), were isolated from 50 % ethanol extract of the roots and rhizomes of S. przewalskii and their structures were identified by MS and NMR spectra. Compound 5 was reported from Labiatae for the first time.